Mengamati Proses Pembelajaran Guru Olahraga Sesuai Rpp (K13) - Hasudungan Sitompul , Brian putra; Siregar, Samsuddin; Perdinan Tarigan, Eykel Dwi; Sirait, Aldi (JPKO Jurnal Pendidikan dan Kepelatihan Olahraga, 2024)
Along with social, cultural, world of work changes and rapid technological advances, the Ministry of Education and Culture (KEMENDIKBUD) designed the Independent Curriculum to prepare students to face future challenges. This curriculum encourages creative, innovative and relevant learning processes, developing aspects of attitudes, knowledge and skills. This research aims to explain the differences between the RPP Curriculum 2013 (K13) and the Merdeka Curriculum and examine the application of the Merdeka Curriculum at SD Negeri 060857 Medan Tembung in learning basic volleyball underpassing techniques. The research method used is qualitative, with an in-depth focus on learning processes and experiences. The research results show that the K13 RPP has a more formal structure with 13 components, while the Merdeka Curriculum is more flexible, allowing teachers to adapt learning to student needs. The implementation of the Merdeka Curriculum in SD Negeri 060857 increases students' skills and independence in learning.